A review on the occurrence and influence of biodegradable microplastics in soil ecosystems: Are biodegradable plastics substitute or threat?. (May 2022) - Fan, Ping; Yu, Hong; Xi, Beidou; Tan, Wenbing
Abstract: Plastic products are widely used around the world, but waste plastic is not reasonably managed and causes serious plastic pollution. Biodegradable plastics (BPs) provide an alternative to conventional plastics, but not all BPs can be completely degraded under natural conditions. Instead, they may break down into microplastics (MPs) faster than conventional plastics, posing an additional threat to soil environment. In this paper, the definition, applications, and degradation behaviors of BPs, including biodegradable microplastics (BMPs), are reviewed, and we comprehensively summarized the eco-toxicological effects of BMPs in soil ecosystems, in terms of physical and chemical properties of soil, soil nutrient cycling, soil bacterial and fungal communities, soil flora and fauna. The compound effects of BMPs and other pollutants were also addressed. The results revealed that BMPs made different or more severely effects compared to conventional MPs. Overall, this review aims to address gaps in knowledge, shed light on the ecological effects of BPs and BMPs in soil. BPs are not a perfect substitute to solve plastic pollution, and further exploration should focus on their generation, environmental behavior, ecological impact and whether BMPs cause more harm than conventional MPs.